2013
DOI: 10.1159/000343703
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Candidate Anti-Allergic Probiotic Strains in a Model of Th2-Skewed Human Peripheral Blood Mononuclear Cells

Abstract: Background: Pre-clinical and clinical studies have evaluated the efficacy of probiotics in allergy. However, predictive in vitro systems for rational strain selection are still missing. Methods: We developed a novel in vitro screening system for the characterization of probiotics with anti-allergic potential. In this model, human peripheral blood mononuclear cells (PBMC) from healthy donors (n = 68) were skewed towards a Th2 cytokine phenotype by culture with IL-4 and anti-CD40, to resemble cells from allergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 80 publications
1
27
1
Order By: Relevance
“…In contrast, the LA307 strain showed a discrete cytokine profile in MLNs and splenocytes, with a low production of Th1, Th2, and Treg cytokines. Holvoet et al suggested that such low-key cytokine patterns induced by probiotics may be associated with a homeostatic effect and may be an alternative cytokine profile for clinical success (33).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the LA307 strain showed a discrete cytokine profile in MLNs and splenocytes, with a low production of Th1, Th2, and Treg cytokines. Holvoet et al suggested that such low-key cytokine patterns induced by probiotics may be associated with a homeostatic effect and may be an alternative cytokine profile for clinical success (33).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this approach is based on the well-recognized effects of specific probiotics on cellular immune responses [6]. As part of the “hygiene hypothesis” it is speculated that the recent rise in allergic diseases may be linked to fewer bacterial encounters in progressively cleaner environments, with a substantial effect on the mucosal immunity conferred in part by the normal intestinal microbial flora [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these data clearly show that the detrimental effects of disturbed barrier function can be counteracted by dietary GOS supplementation and that a reduction of IL-33 levels seems to be critically involved in this protective effect. A more direct approach was taken by Holvoet et al [7] who cocultured human T cells, skewed towards the Th2 phenotype by a classic protocol in a 3-day culture with IL-4 and anti-CD40 mAbs [8], with a collection of 35 different probiotic bacterial strains and analyzed the secretion levels of signature cytokines. Of note, all strains downregulated IL-5 secretion levels similarly to or even stronger than LPS, which was used as a control.…”
Section: Cd4+ T Helper Cellsmentioning
confidence: 99%
“…Besides simply modulating cytokine profiles, it cannot be excluded that probiotics might also be involved in the reinforcement of the intestinal barrier, which would, however, require alternative tests for accurate evaluation. Nevertheless, the established in vitro assay allows the preselection of probiotics revealing a potentially beneficial cytokine pattern as candidates for detailed in vivo evaluations in the future [7]. …”
Section: Cd4+ T Helper Cellsmentioning
confidence: 99%